2018
DOI: 10.1590/s1984-296120180084
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effect of diflubenzuron, administered via mineral salt supplementation, against Haematobia irritans and Rhipicephalus microplus parasitizing cattle

Abstract: This study involved two field trials with the aim of evaluating the efficacy of diflubenzuron, via mineral supplementation, against Haematobia irritans parasitizing cattle. Concomitantly with the main trial, a stall test was conducted to ascertain the effects of a different formulation with the same active ingredient against Rhipicephalus microplus, along with the action of diflubenzuron on the reproductive parameters of R. microplusfemales that had naturally detached from cattle. Against H. irritans, it was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…There are reports of increased prevalence of R. microplus populations that are resistant to different chemical classes of insecticides, such as the amidines, macrocyclic lactones, phenylpyrazoles and benzophenylurea [ 5 , 47 55 ]. It is apparent from the published literature that R. microplus populations in those regions where studies with Exzolt were conducted were resistant to amitraz (250 ppm) [ 56 , 57 ], abamectin and ivermectin 500 µg/kg BW pour-on, ivermectin 200 and 630 µg/kg BW injectable [ 58 60 ], fipronil 1 mg/mg pour-on [ 37 ], fluazuron 1.6 mg/kg + ivermectin 630 µg/kg (injectable) and diflubenzuron with 17 g of product added per kilogram of mineral salt [ 61 , 62 ]. The studies reported here may indicate the effectiveness of Exzolt in ticks resistant to above-mentioned parasiticides.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of increased prevalence of R. microplus populations that are resistant to different chemical classes of insecticides, such as the amidines, macrocyclic lactones, phenylpyrazoles and benzophenylurea [ 5 , 47 55 ]. It is apparent from the published literature that R. microplus populations in those regions where studies with Exzolt were conducted were resistant to amitraz (250 ppm) [ 56 , 57 ], abamectin and ivermectin 500 µg/kg BW pour-on, ivermectin 200 and 630 µg/kg BW injectable [ 58 60 ], fipronil 1 mg/mg pour-on [ 37 ], fluazuron 1.6 mg/kg + ivermectin 630 µg/kg (injectable) and diflubenzuron with 17 g of product added per kilogram of mineral salt [ 61 , 62 ]. The studies reported here may indicate the effectiveness of Exzolt in ticks resistant to above-mentioned parasiticides.…”
Section: Discussionmentioning
confidence: 99%